2007
DOI: 10.1007/s10695-007-9185-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent lipid levels and components in polar and temperate eelpout (Zoarcidae)

Abstract: Total lipid content, lipid classes and fatty acid composition were analysed in tissues from two eelpout species fed on the same diet, the Antarctic Pachycara brachycephalum and the temperate Zoarces viviparus, with the aim of determining the role of lipids in fishes from different thermal habitats. The lipid content increased with decreasing temperature in the liver of both species, suggesting enhanced lipid storage under cold conditions. In P. brachycephalum, lipid composition in the liver and muscle was stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
8
24
0
Order By: Relevance
“…The lipid fraction in liver of P. brachycephalum kept at 0°C is threefold higher than in Z. viviparus at habitat temperature [37], in line with the general finding that Antarctic species have high capacities for catabolism of fatty acids [38]. Furthermore, a recent study demonstrated relationships between preferred energy fuels and transcript levels of respective genes in P. brachycephalum [39].…”
Section: Discussionsupporting
confidence: 54%
“…The lipid fraction in liver of P. brachycephalum kept at 0°C is threefold higher than in Z. viviparus at habitat temperature [37], in line with the general finding that Antarctic species have high capacities for catabolism of fatty acids [38]. Furthermore, a recent study demonstrated relationships between preferred energy fuels and transcript levels of respective genes in P. brachycephalum [39].…”
Section: Discussionsupporting
confidence: 54%
“…Successful cloning of the different PPARs demonstrated that P. brachycephalum expresses the same compounds of the PPAR signaling cascade as temperate eurythermal fish. Lipid accumulation in the cold found for the Antarctic eelpout (10) and for species in the suborder of the Notothenioidei (38) indicate the general preference for fatty acids as main energy stores in cold-adapted fishes. First, temperature-induced shifts in lipid degradation and synthesis pathways over time may provide intermediates sensed by the PPAR family of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Few published studies were available on possible changes in lipid fractions in the animals in changing climate. Roughly based on study by Brodte et al [36] on temperaturedependent lipid levels in polar and temperate eelpout (Pachycara brachycephalum and Zoarces viviparus [Zoarcidae]), a (linear) decrease was assumed in L of 5% per 8C increase in the present scenarios for poikilotherm aquatic fauna (i.e., no change in L was assumed for algae and kittiwake). No changes were assumed in the organisms' body volumes (V) in the present scenarios.…”
Section: Simulated Climate Scenariosmentioning
confidence: 99%